A non-interventional, prospective, multicentric real life Indian study to assess safety and effectiveness of un-denatured type 2 collagen in management of osteoarthritis - Mehra, Apurv; Anand, Pankaj; Borate, Mangesh; Paul, Prasenjit; Kamble, Sanjay; Dev Mehta, Kapil; Qamra, Amit; Shah, Agam; Jain, Rishi (International Journal of Research in Orthopaedics, 2019)
Background: Osteoarthritis (OA) is the most common musculoskeletal condition affecting the quality of life. Undenatured collagen type II has emerged as one of the promising treatment options in treatment of OA. Despite being available in India, clinical safety and efficacy have not been evaluated. We performed a non-interventional, real-life study to determine its safety and efficacy in Indian population. Methods: A non-interventional, real-life study was performed in patients with OA of knee by 18 orthopaedicians in India. Patients enrolled were followed-up at day 30 (visit 2), day 60 (visit 3) and day 90 (visit 4). Efficacy was assessed by Western Ontario McMaster Osteoarthritis Index (WOMAC) and Visual Analogue scale (VAS) on each visit. Safety was assessed by incidence of suspected adverse events (AEs), and abnormal laboratory parameters. Results: Among 291 enrolled patients 226 patients completed the study. Mean age of the population was 56.2±8.7 years and 53.3% of them were females. In 291 patients included in safety analysis, at least one treatment emergent adverse event (TEAE) was seen in 4.47% patients. None of the AEs were serious or resulted in termination of patient from the study. Nausea (1.37%) and headache (1.03%) were the common AEs. Treatment with undenatured collagen type II was associated with significant reduction in WOMAC score (p<0.0001) and VAS scores (p<0.0001) from baseline to day 90. Conclusions: Undenatured collagen type II is safe and efficacious in Indian patients with OA. This can be considered early in the initial management of OA.